Backward linkage - Ahmed, Khandker Habib (KDI School, 2000)
The clothing products of Bangladesh, at present, have restricted and reserved access (quota) to the readymade garment markets of developed countries, particularly, the United States. From 01 January 2005, as per the provisions of the WTO Agreement on Textiles and Clothing (ATC), Bangladesh's garment and textile manufacturers will have to cope with steep competition from such countries as India, Pakistan, China, and Thailand, from which Bangladesh now imports raw materials to satisfy the demand of its textiles and clothing sector. All these countries will be able to inflate their RMG exports, now limited by quotas, when the WTO establishes its free market in 2005. As a consequence, these countries are likely to utilize more of their locally produced yarn and fabrics internally, resulting in the rise of prices for such raw materials as Bangladesh imports from them, putting pressure on the textiles and clothing industries of the country. Again, backward linkage industries have a l ready thrived in these contesting countries, which would, presumably, let them to stay in competition in the impending free market with a better position than Bangladesh. Setting up backward linkage industries in Bangladesh with a complete supply chain to its major export earning RMG sector is , therefore , crucial
Thesis(Master) --KDI School:Master of Public Policy,2000